“De gravata e unha vermelha”: transgeneridades e sexualidades - Melo, Ailton Dias de (2016)
In western history has developed in its path from nineteenth century, a discourse on sex which was linked to control relations, on rigid heteronormative patterns, with premises of "naturalness", causing individuals who, for some reason to escape from expectations and if they constituted in a different way from the expected one, they bump into the maintenance of the power, having to face big challenges to be and to live as they wish. Transgender points to possibilities of transgression of this perspective, subverting the linear system of relations among sex-body-gender, thus making see the sexuality as a multiple way. Therefore, we assume the plural. In the present research, it is proposed to broaden the horizons of the discussion about transgender by means of articulations with reference as poststructuralist, feminist, queer and Foucaultian theorizations, problematizing the relations among knowledge, powers and truths in the themes of genres and sexualities. This process was constituted by means of explorations and problematizations. An odyssey aboard a (trans) ship, guided by post-critical methodologies. Navigation in waters, often revolts, involved by movements as assembly, disassembly and reassembly. All the processes were deflagrated by statements and speeches unveiled by the Brazilian documentary - with a tie and red fingernail - by the psychoanalyst, screenwriter and director Miriam Chnaiderman, who explores the transgender universe in several interviews. With this, it was possible to see new and broader "glances" over people considered as gender-divergent, regardless of the way in which they constitute their subjectivities. This research endorses the struggle for possibilities to live beyond this or that, for all those considered to be offenders of the binary gender device and who today live subject to multiple and heavy socio-political, economic and cultural sanctions, which are often restricted even for their right ‗to come and go‘ in society. In this text, many current conceptions about transgender and sexuality are questioned and it indicates that there are many other questions to be done. We only need the courage to admit the plural of the question that exists beyond the binarism that insists on wanting to dominate the bodies, their expressions, relationships, experiences and pleasures.